Biomass in Small-Scale Energy Applications Theory and Practice. - Szubel, Mateusz; Filipowicz, Mariusz (Milton : CRC Press LLC, 2019)
Biomass in Small-Scale Energy Applications: Theory and Practicepresents the current trends in the development of selected biomass-based technologies for distributed energy generation. It describes the methodology, experimental results, and computer simulations with a focus on pilot systems and devices crucial in multiple applications with related environmental/economic issues.It describes which stages of design, development, and application of advanced biomass-based energy devices are critical in order for a given technology to be successful. It includes both technical/practical information and theoretical background related to combustion kinetics, thermodynamics in energy systems, and properties of selected types of biomass, as well as case studies.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Biotechnology; SCIENCE / Energy; TECHNOLOGY / Engineering / Civil; Small power production facilities; Biomass energy; Electric power-plants -- Fuel